RANKING of the E-TRUST FACTORS in ELECTRONIC TRANSACTIONS in the CONTEXT of B2C E-COMMERCE (from the consumers point of view and by using Friedmans ranking method) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Today, a considerable amount of commercial transactions have appertained to the electronic transactions and electronic markets, aside from or versus the traditional markets, have attracted and collected a large number of buyers, distributers and sellers with the aim of exploring commercial opportunities for trading interactions and gaining more profit. The environment of electronic markets has inherited the risks and vulnerability for its infrastructure, i.e. the internet. This high risk environment complicates the process of building trust in transactions for transaction parties. The virtual and online nature of the new environment emphasizes the importance of the term online trust. The factors of online trust in different classes of e-commerce are different from each other depending on the type of transaction parties. In various studies the factors of trust in e-commerce transactions of type B2C have been identified and discussed. These factors can be classified in three groups of personal, corporate and trust context factors. In this research, after categorizing the electronic trust factors to five groups of personal, corporate, legal, contextual and infrastructural, and by collecting the necessary data from 10 e-commerce websites we have ranked the trust factors from the perspective of those websites customers. According to the opinions of the customers of those websites, the priority of electronic trust factors is mixed marketing factors and e-security and privacy policy factors.